KELAYAKAN FLIPBOOK MATERI BERBAGAI TINGKAT KEANEKARAGAMAN HAYATI INDONESIA DARI BUAH PELUNTAN, SENARE, DAN ARA’ - Niagara, Niagara; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of flipbook on the material of variaty of Indonesia biodiversity levels class X from the results of morphological research and nutritional content of peluntan, senare, and ara' fruits coming from Desa Serimbu forest, Landak Regency in West Kalimantan. The form of research was descriptive with purposive sampling technique. Flipbook was validated by five validators with 14 criteria and calculated using CVR and CVI Lawshe analysis methods. Two validators was lecturers of biology education, while three other validators an X-class high school biology teachers who uses the curriculum in 2013 in the city of Pontianak. Flipbook validation results obtained CVR and CVI value up to 0.99 corresponds to the value of the CVR minimum Lawshe to five validator that was 0.99, so that the flipbook was valid and could be used as a media of learning on the material of various levels of biodiversity of Indonesia class X. Keywords: Biodiversity, Flipbook, Peluntan, Senare, Ara’